Binding of hnRNP H and U2AF65 to Respective G-codes and a Poly-Uridine Tract Collaborate in the N50-5'ss Selection of the REST N Exon in H69 Cells - Buratti, Emanuele; Ortuño Pineda, Carlos; Galindo Rosales, José Manuel; Calderón Salinas, José Victor; Villegas Sepúlveda, Nicolás; Saucedo Cárdenas, Odila; De Nova Ocampo, Mónica; Valdés, Jesús (Public Library of Science, 2012)
The splicing of the N exon in the pre-mRNA coding for the RE1-silencing transcription factor (REST) results in a truncated protein that modifies the expression pattern of some of its target genes. A weak 3’ss, three alternative 5’ss (N4-, N50-, and N62-5’ss) and a variety of putative target sites for splicing regulatory proteins are found around the N exon; two GGGG codes (G2-G3) and a poly-Uridine tract (N-PU) are found in front of the N50-5’ss. In this work we analyzed some of the regulatory factors and elements involved in the preferred selection of the N50-5’ss (N50 activation) in the small cell lung cancer cell line H69. Wild type and mutant N exon/b-globin minigenes recapitulated N50 exon splicing in H69 cells, and showed that the N-PU and the G2-G3 elements are required for N50 exon splicing. Biochemical and knockdown experiments identified these elements as U2AF65 and hnRNP H targets, respectively, and that they are also required for N50 exon activation. Compared to normal MRC5 cells, and in keeping with N50 exon activation, U2AF65, hnRNP H and other splicing factors were highly expressed in H69 cells. CLIP experiments revealed that hnRNP H RNA-binding occurs first and is a prerequisite for U2AF65 RNA binding, and EMSA and CLIP experiments suggest that U2AF65-RNA recognition displaces hnRNP H and helps to recruit other splicing factors (at least U1 70K) to the N50-5’ss. Our results evidenced novel hnRNP H and U2AF65 functions: respectively, U2AF65-recruiting to a 5’ss in humans and the hnRNP H-displacing function from two juxtaposed GGGG codes.